Perbandingan Penerapan Metode Net Dan Gross Up Pada Pajak Penghasilan Karyawan di PT. YTI - Singgih bagus Pangestu; Maya Widyana Dewi; Sri Laksmi Pardanawati (Nur Science Institute, 2026)
This study aims to compare the calculation of Income Tax Article 21 using the Net Method and the Gross Up Method on the salaries and allowances of permanent employees at PT YTI. This research uses a qualitative descriptive approach by collecting, processing, and analyzing data to obtain a clear understanding of the problem under study. The data used in this study consist of primary and secondary data obtained directly from the company as well as supporting documents and reports. The analysis was conducted by comparing the calculation results of PPh Article 21 using the two methods in order to determine the most efficient method for the company. The results show that the calculation of PPh Article 21 using the Net Method produces a tax payable of Rp9,350,400, while the Gross Up Method results in a higher tax payable of Rp9,842,526. The difference between the two methods is Rp492,126. Although the Gross Up Method provides higher income benefits for employees because the company provides tax allowances, it increases the tax burden for the company. Therefore, the Net Method is considered more efficient and beneficial for the company in managing its PPh Article 21 obligations.